Current-induced abnormal and oriented grain growth in corundum upon flash sintering. (June 2018) - Biesuz, Mattia; Sglavo, Vincenzo M.
Abstract: An electrical current upon flash sintering experiments modifies the defect chemistry of corundum and causes the formation of color centers (F-centers), consisting of discharged oxygen vacancies. This phenomenon interacts with the diffusion kinetics in the anodic region and promotes abnormal growth of some grains which reach several hundreds of micrometers in just few minutes, the grains being strongly oriented orthogonally to the current flow. Graphical abstract: Unlabelled Image